Perception of School Citizens about Violence against Students - Zuman Malaka; Bambang Satriya; Kridawati Sadhana (International Journal of Islamic Thought and Humanities, 2023)
One of the social realities about violence against students at MTS Nurul Khoir Surabaya that attracts attention, namely violence in the form of "stabbing" carried out by fellow students because the perpetrator feels disappointed with the victim who often commits physical violence or verbal violence against perpetrators and other students. This study aims to describe and analyze the perceptions of school members about violence against students at MTS Nurul Khoir Surabaya and the indicators underlying the perceptions of school members about violence against students at MTS Nurul Khoir Surabaya using a qualitative approach. The findings of this study indicate that 1) The perceptions of school members about violence against students at MTS Nurul Khoir Surabaya are different, such as there are informants who give positive assessments, namely violence against students is a natural thing because students are entering their teens who are still looking for identity, as well as violence against students can make students mentally strong. While the negative assessment, namely the existence of informants' disapproval of violence against students at MTS Nurul Khoir Surabaya because it is an action that can injure students physically and mentally and disrupt teaching and learning activities at school, 2) Indicators underlying the perceptions of school residents about violence towards students at MTS Nurul Khoir Surabaya including a) there is the absorption of objects namely violence against students at MTS Nurul Khoir Surabaya, b) there is an understanding or understanding of violence against students at MTS Nurul Khoir Surabaya, and c) there is an assessment or an evaluation of violence against students at MTS Nurul Khoir Surabaya from each school member informant, thus creating different perceptions.